In: Computer Science
Given the following sentences:
a) Negate the conclusion " If John is a light sleeper, then John does not have any mice"
First we convert conclusion in well formed formula (wff) :
LS(John) → ¬ ∃ (z) (Have(John,z) ∧ Mouse(z)) (LS means Light Sleeper)
¬ [LS(John) → ¬ ∃ z (Have(John,z) ∧ Mouse(z))] (negate the conclusion)
¬ [¬ LS (John) ∨ ¬ ∃ z (Have (John, z) ∧ Mouse(z))] (using P --> Q => ¬P ∨ Q )
LS(John) ∧ ∃ z (Have(John, z) ∧ Mouse(z)))
Hence, LS(John) ∧ Have(John,b) ∧ Mouse(b)
b) To prove conclusion using Resolution, First we convert sentences into well formed formula (wff) :-
=> Then we convert well formed formula (wff) into conjunctive normal form (CNF):-
¬ Hound(x) ∨ Howl(x)
∀ x: ∀ y: (Have(x,y) ∧ Cat (y) → ∀ z ¬ (Have(x,z) ∧ Mouse(z)))
∀ x: ∀ y ∀ z (¬ (Have(x,y) ∧ Cat(y)) ∨ ¬ (Have(x,z) ∧ Mouse(z)))
¬ Have(x,y) ∨ ¬ Cat(y) ∨ ¬ Have(x,z) ∨ ¬ Mouse(z)
∀ x (LS(x) → ∀ y ¬ (Have(x,y) ∧ Howl(y)))
∀ x ∀ y (LS(x) → ¬ Have(x,y) ∨ ¬ Howl(y))
∀ x ∀ y (¬ LS(x) ∨ ¬ Have(x,y) ∨ ¬ Howl(y))
¬ LS(x) ∨ ¬ Have(x,y) ∨ ¬ Howl(y)
Have(John,a) ∧ (Cat(a) ∨ Hound(a))
¬ [¬ LS (John) ∨ ¬ ∃ z (Have(John, z) ∧ Mouse(z))]
LS(John) ∧ ∃ z (Have(John, z) ∧ Mouse(z)))
LS(John) ∧ HAVE(John,b) ∧ Mouse(b)
=> So, we have set of CNF clauses:-
=> Resolution Proof:- In this we cancel the negate predicate with normal predicate
using [1.,4.(b):] | 6. | CAT(a) ∨ HOWL(a) |
using [2,5.(c):] |
7. | ¬ HAVE(x,y) ∨ ¬ CAT(y) ∨ ¬ HAVE(x,b) |
using [7,5.(b):] |
8. | ¬ HAVE(John,y) ∨ ¬ CAT(y) |
using [6,8:] |
9. | ¬ HAVE(John,a) ∨ HOWL(a) |
using [4.(a),9:] |
10. | HOWL(a) |
using [3,10:] |
11. | ¬ LS(x) ∨ ¬ HAVE(x,a) |
using [4.(a),11:] |
12. | ¬ LS(John) |
using [5.(a),12:] |
13. | □ (null) |